2020
DOI: 10.1080/10826084.2020.1823419
|View full text |Cite
|
Sign up to set email alerts
|

HIV Pre-Exposure Prophylaxis Prevention Awareness, Willingness, and Perceived Barriers among People Who Inject Drugs in Los Angeles and San Francisco, CA, 2016–2018

Abstract: Background: Pre-exposure prophylaxis (PrEP) for HIV prevention is indicated for people who inject drugs (PWID), yet most studies exclude PWID. This study examines factors associated with PrEP awareness and willingness, and identifies perceived barriers to PrEP among PWID.Methods: PWID were interviewed in Los Angeles and San Francisco, CA from 2016 to 2018. We analyzed data from self-reported HIV-negative participants who had injected drugs within the past 6 months (n=469). Questions on PrEP included awareness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 71 publications
2
16
1
Order By: Relevance
“…As a user-controlled HIV prevention method, PrEP may be particularly important for women who engage in exchange sex and/or use drugs, especially those who inject drugs who may be at risk for HIV and struggle in negotiating condoms or drug use equipment [ 25 , 26 ]. However, despite PrEP’s potential benefit, PrEP uptake in the U.S. have been persistently low among women [ 27 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a user-controlled HIV prevention method, PrEP may be particularly important for women who engage in exchange sex and/or use drugs, especially those who inject drugs who may be at risk for HIV and struggle in negotiating condoms or drug use equipment [ 25 , 26 ]. However, despite PrEP’s potential benefit, PrEP uptake in the U.S. have been persistently low among women [ 27 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, women who perceive their risk as low have reported behaviors, such as condomless sex and sharing injection equipment, indicating they may be at greater risk than perceived [ 34 , 36 ], thus highlighting the importance of HIV prevention education including information about PrEP. Concerns about side effects and cost of PrEP [ 35 , 37 39 ], reduced efficacy if not taken daily [ 31 ], PrEP-related stigma [ 39 41 ], and medical mistrust [ 37 ], including mistrust due to transphobia experienced by women of trans experience [ 42 ], have also been identified in previous studies. Along with barriers some studies have identified facilitators to PrEP uptake, such as learning about PrEP from a trusted source [ 43 ] and having a welcoming, client-centered, culturally appropriate environment that is stigma free allowing for positive interactions with PrEP prescribers [ 35 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies among sexual minority men and transgender women, which focus on sexual transmission, have found about 99% efficacy when taken regularly [ 3 , 4 ]. Despite the benefit of PrEP, uptake among PWID has been low, with recent studies reporting between 1 and 2% [ 5 , 6 ]. One barrier to PrEP uptake is low PrEP awareness [ 5 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, when informed about PrEP, many PWID are interested in taking it. For example, one study reported 63% willingness to take PrEP among PWID in Baltimore, Maryland [ 5 ], and another study found 59% among PWID in San Francisco and Los Angeles, California [ 6 ]. In addition to awareness, barriers to uptake include co-pays for doctors’ visits, the need to take PrEP daily, and concerns about increased risk for HIV or sexually transmitted infections with PrEP [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation